Faktor Yang Mempengaruhi Pemilihan Jenis Kontrasepsi Pada Wanita Usia Subur - Reva Dwi Yanty (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2019)
Projection results show that the population of Indonesia over the next twenty-five years continues to increase, which is from 238.5 million in 2010 to 305.6 million in 2035. Seeing this, the government has long launched a program to suppress the rate of population growth, which is the Family Planning program (KB). Family Planning program (KB) according to LAW No. 10 of 1992 (on the development of population and development of prosperous family) is an effort to raise awareness and participation of the community through the maturity of marital age (PUP), setting Birth, family endurance coaching, raising small, happy, and prosperous families. Types of contraception are available based on the contents of which there are two, hormonal contraceptives (pills, injections, implants and recently introduced IUD-Mirena or LNG-IUS) and non-hormonal contraceptives (condoms, IUD-tcu, and Kontap methods). While according to the length of effectiveness of contraception can be divided into and MKJP namely IUD, Implant, MOP and MOW Non MKJP namely condoms, pills, injections and other methods. Lawrence Green's theory says that the determinant that affects a person in taking an action is influenced by 3 major factors in the behaving i.e., the first predisposition factor (predisposing factor), the second supporting factor (enabling factor), and the third amplifier factor (reinforcing factor).